Non-Pharmacological Therapy In Overcoming Uremic Pruritus In Hemodialysis Patients: Systematic Review - Afiatika Ahsani; Armi Mawaddah (STIKes RSPAD RSPAD Gatot Soebroto, 2026)
Introduction: Uremic pruritus or Chronic Kidney Disease-associated Pruritus (CKD-aP) is a common complication in hemodialysis patients, with a prevalence of 30-70%. Pharmacological therapy is often ineffective or has side effects, so non-pharmacological therapy is an important alternative. Objective: This systematic review aims to identify and evaluate non-pharmacological therapeutic interventions in reducing the intensity of uremic pruritus in hemodialysis patients. Methods: The systematic review uses the PRISMA 2020 guidelines. The databases used in the article search consist of EBSCO, PUBMED, ProQuest, CINAHL, and Wiley using relevant keywords based on the topic and title of the study. Article selection uses the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram method, with a total of 4,127 articles obtained. 5 articles were obtained according to the inclusion criteria and analyzed descriptively narratively and have met the quality review using the JBI (Joanna Briggs Critical Appraising Methodology) guidelines. Results: Five research articles with non-pharmacological therapeutic interventions consisting of topical Anethum Graveolens oil, topical Sweet Almond oil, topical violet oil, acupressure and auricular pressure. Conclusion: The findings of this systematic review indicate that non-pharmacological interventions in the form of topical Anethum Graveolens oil, topical Sweet Almond oil, topical violet oil, acupressure and auricular pressure can reduce the severity of uremic pruritus in hemodialysis patients. Non-pharmacological therapy has the potential to be an effective, safe, and easy-to-implement intervention to reduce uremic pruritus in hemodialysis patients. However, high-quality studies are needed to ensure long-term effectiveness.